Between Caution and Speculation Investor Personality Mapping among Muslim Millennial Crypto Traders - Aldi Khusmufa Nur Iman; Umi Indasyah Zahro; Afaful Ummah; Hawa Gazani; Clara Devy Yulvia Ratna Sary; Afuza Medina (Utiliti Project Solution, 2026)
Volatility, digital information flows, and ethical debate make cryptocurrency decisions difficult to explain through the rational-investor assumption alone. The Bailard, Biehl, and Kaiser (BB&K) model was selected because its two dimensions, confidence and method of action from careful to impetuous, are directly observable in decision narratives. This study maps the psychographic profiles of Muslim millennial cryptocurrency investors in East Java and explains how market context shapes the visibility of investor types. It adopts an interpretive qualitative design with a phenomenological orientation. Thirteen active investors were recruited through purposive and snowball sampling. Anonymized interview summaries were thematically organized in NVivo and compared across cases before being mapped onto the five BB&K profiles. The results identify 2 Adventurers, 2 Celebrities, 3 Individualists, 6 Guardians, and no Straight Arrow. The distribution reveals polarization among speculative action, social dependence, independent analysis, and capital protection. The missing Straight Arrow suggests that investment personality is not expressed as a fixed trait. Volatility, continuous trading tempo, digital social pressure, and ethical reflection can intensify positions away from the moderate center. The study extends BB&K profiling to digital assets and supports personality-sensitive Islamic financial literacy that addresses the distinct behavioral vulnerability of each investor type.